2015
DOI: 10.1038/bjc.2014.541
|View full text |Cite
|
Sign up to set email alerts
|

The combination of axitinib followed by paclitaxel/carboplatin yields extended survival in advanced BRAF wild-type melanoma: results of a clinical/correlative prospective phase II clinical trial

Abstract: Background:Simultaneous chemotherapy with vascular endothelial growth factor (VEGF) inhibition has not shown additional benefit over chemotherapy alone in advanced melanoma. We tested administration of the potent VEGF inhibitor axitinib followed by paclitaxel/carboplatin to determine whether enhanced tumour proliferation during axitinib withdrawal leads to sustained chemosensitivity.Methods:We conducted a prospective phase II trial in metastatic melanoma patients with ECOG performance status 0–1 and normal org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…As this meta-analysis excluded studies with patients treated with a BRAF and MEK inhibitor or a checkpoint inhibitor, only eight studies, with patients treated with chemotherapy, immunotherapy or surgery were pooled. Except for one small study [35] with 38 patients that showed significantly poorer PFS (HR: 5.5) in BRAF mutated versus WT patients, no prognostic impact on PFS was reported. The pooled effect showed that BRAF mutational status had a neutral role on PFS.…”
Section: Discussionmentioning
confidence: 98%
“…As this meta-analysis excluded studies with patients treated with a BRAF and MEK inhibitor or a checkpoint inhibitor, only eight studies, with patients treated with chemotherapy, immunotherapy or surgery were pooled. Except for one small study [35] with 38 patients that showed significantly poorer PFS (HR: 5.5) in BRAF mutated versus WT patients, no prognostic impact on PFS was reported. The pooled effect showed that BRAF mutational status had a neutral role on PFS.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, drugs targeting vascular endothelial growth factor (VEGF) or its receptor have shown encouraging clinical outcomes in early-phase studies when combined with chemotherapy, 49 demonstrating survival extension in patients with metastatic melanoma. 50 Immune targeting of the NOTCH antagonist delta-like 1 homolog (DLK1) has also shown promising results in normalizing the vasculature in the TME of renal cell carcinoma mice models. 51 Furthermore, while in the present study Rictor ¡/¡ DC promoted the loss of MDSC in the TME, the negative impact of Treg on type-1 CD8…”
Section: Discussionmentioning
confidence: 99%
“…52 However, these result warrants further testing in randomized phase III trials. On the other hand, the multi-kinase inhibitor Lenvatinib (E7080) achieved limited responses both in monotherapy and in combination with TMZ in the phase I setting.…”
Section: Other Multi-kinase Inhibitorsmentioning
confidence: 97%